Modeliranje povezanega zidovja z numeričnim 3D-modelom - Krtinić, Nemanja (Gradbeni vestnik, 2024)
This article presents an investigation into seismic resistance of modern confined masonry built from hollow clay blocks with large holes for thermal insulation, which is glued by polyurethane glue instead of mortar. Based on the results of two experimental tests from cyclic shear tests a detailed micro numerical model based on the finite element method was developed in the Abaqus software. The developed model was able to accurately predict the global response of the walls in terms of a force- displacement pushover curve as well as the damage evolution and pattern in the masonry and in the tie-columns. Because the tie-columns were thinner than the masonry, special type of damage occurred at the contact between these two elements. This effect was also successfully reproduced by the model.
Keywords: civil engineering; confined masonry; gradbeništvo; hollow clay block; numerical modelig; numerično modeliranje; opečni votlak; potresna odpornost; povezano zidovje; PU glue; PU lepilo; seismic resistance